Elucidating the Role of Dimensionality on the Electronic Structure of the Van der Waals Antiferromagnet NiPS3 - DiScala, Michael F.; Staros, Daniel; de la Torre, Alberto; Lopez, Annette; Wong, Deniz; Schulz, Christian; Barkowiak, Maciej; Bisogni, Valentina; Pelliciari, Jonathan; Rubenstein, Brenda; Plumb, Kemp W. (Advanced Physics Research, 2024)
The sustained interest in investigating magnetism in the 2D limit of insulating antiferromagnets is driven by the possibilities of discovering, or engineering, novel magnetic phases through layer stacking. However, due to the difficulty of directly measuring magnetic interactions in 2D antiferromagnets, it is not yet understood how intralayer magnetic interactions in insulating, strongly correlated, materials can be modified through layer proximity. Herein, the impact of reduced dimensionality in the model van der Waals antiferromagnet NiPS3 is explored by measuring electronic excitations in exfoliated samples using Resonant Inelastic X‐ray Scattering (RIXS). The resulting spectra shows systematic broadening of NiS6 multiplet excitations with decreasing layer count from bulk down to three atomic layers (3L). It is shown that these trends originate from a decrease in transition metal‐ligand and ligand–ligand hopping integrals, and by charge‐transfer energy evolving from Δ = 0.83 eV in the bulk to 0.37 eV in 3L NiPS3. Relevant intralayer magnetic exchange integrals computed from the electronic parameters exhibit a decrease in the average interaction strength with thickness. This study underscores the influence of interlayer electronic interactions on intralayer ones in insulating magnets, indicating that magnetic Hamiltonians in few‐layer insulating magnets can greatly deviate from their bulk counterparts. The impact of reduced dimensionality in the model van der Waals antiferromagnet NiPS3 is explored by measuring electronic excitations in exfoliated samples using Resonant Inealstic X‐ray Scattering (RIXS). The systematic broadening of RIXS spectra with decreasing thickness revealed an electronic structure intricately linked to dimensionality. This work showcases RIXS as an essential tool to investigate exfoliated 2D magnets.